ĐỊNH LƯỢNG ĐỒNG THỜI KAEMPFEROL VÀ KAEMPFERITRIN TRONG LÁ CÂY Aralia hiepiana J. Wen & Lowry BẰNG PHƯƠNG PHÁP SẮC KÝ LỎNG HIỆU NĂNG CAO (HPLC) - Nguyễn Thị Thu Hiền (Hà Nội, Việt Nam, 2023)
A reversed-phase high performance liquid chromatographic method using DAD detector with gradient election has been developed and validated for the simultaneous quantification of two flavonoid compounds (kaempferol and kaempferitrin) in different partitions from methanol extract of leaves of Aralia hiepiana, collected in Dalat city, Vietnam. Separation of the two compounds was achieved with a Hypersil BDS C18 column (5 µm particle size, 4x125mm, Thermo Fisher, USA) by gradient elution using acetonitrile-water containing 1% acetic acid as a mobile phase. The flow rate and detection wavelength was set at 0.5 mL/min and 265 nm, respectively. The calibration curve of each analyte had a correlation coefficient close to 1. The recovery of the two flavonoids was 103.4 and 97.6, respectively. This method showed high reliability and can be implemented in practical application.